2017
DOI: 10.1186/s12904-017-0202-3
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in the neonatal unit: neonatal nursing staff perceptions of facilitators and barriers in a regional tertiary nursery

Abstract: BackgroundNeonatology has made significant advances in the last 30 years. Despite the advances in treatments, not all neonates survive and a palliative care model is required within the neonatal context. Previous research has focused on the barriers of palliative care provision. A holistic approach to enhancing palliative care provision should include identifying both facilitators and barriers. A strengths-based approach would allow barriers to be addressed while also enhancing facilitators. The current study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
55
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 14 publications
4
55
0
13
Order By: Relevance
“…One of the aspects covers the possible introduction of amendments/ optimization of the physical structure and changes in the current operating regulations. Data collected is in accordance with another study accessed and showed that there are some obstacles that hinder the full implementation of NPC: the absence of facilities that would provide the child and his parents with the right isolation and privacy and some factors associated with the department's procedures and policies (27) . The ideal situation would be to have the NB and his family transferred to a private room and make sure that relatives will be protected and will not be forgotten (6) .…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…One of the aspects covers the possible introduction of amendments/ optimization of the physical structure and changes in the current operating regulations. Data collected is in accordance with another study accessed and showed that there are some obstacles that hinder the full implementation of NPC: the absence of facilities that would provide the child and his parents with the right isolation and privacy and some factors associated with the department's procedures and policies (27) . The ideal situation would be to have the NB and his family transferred to a private room and make sure that relatives will be protected and will not be forgotten (6) .…”
Section: Discussionsupporting
confidence: 71%
“…There is a wide range of suggestions for improving the team performance that focus mainly on the need for training (27)(28) . Another important aspect is team sharing and reflection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often evidenced by lack of staff and adequate care even though it is easy for the immediate family members to access the hospital [19]. In our opinion, this situation makes the neonatal care more complicated especially when the local nurses decide whether or not the neonates will be transferred to the local hospital.…”
Section: Discussionmentioning
confidence: 94%
“…In our opinion, this situation makes the neonatal care more complicated especially when the local nurses decide whether or not the neonates will be transferred to the local hospital. As discussed by Kilkulen M and coauthors, the use of telemedicine and the use of documented guidelines are the most critical factors that facilitate the smooth transfer of neonates to a palliative care unit close to their home [19][20][21].…”
Section: Discussionmentioning
confidence: 99%